Anomalous quartic WWγγ and ZZγγ couplings in γp collision at the LHC - Senol, A. (World Scientific Pub Co Pte Lt, 2014)
We analyze the anomalous quartic gauge boson couplings WWγγ and ZZγγ, described by dimension-six effective quartic Lagrangian at the LHC. The sensitivities to anomalous quartic gauge couplings [Formula: see text] by examining the two different photon-induced processes pp → pγp → pWγqX and pp → pγp → pZZqX with W and Z's decaying leptonically are investigated. We show that γp mode of photon-induced reactions at the LHC are able to probe these couplings to the order of 10-6–10-7GeV-2at 95% confidence level (C.L.) with [Formula: see text] and for proton–proton luminosities in the range of 30–200 fb-1.
Keywords: 13. Climate action; 7. Clean energy